Digital Skills Development for Waqf Professionals in India: A Capacity Building Framework leveraging WAMSI (Waqf Asset Management System of India) Software - Rakshan, Anam (Journal of International Conference Proceedings, 2024)
India's Waqf sector, managing over 500,000 endowments, faces challenges in leveraging digital technologies, hindering its potential. Waqf professionals' limited digital literacy necessitates targeted capacity building. This research proposes a framework for digital skills development, leveraging WAMSI, to enhance Waqf management, governance, and social impact. This research paper explores the digital transformation of waqf management, examining the opportunities and challenges that arise from this transition. The study assesses the readiness of waqf institutions for digital transformation in India . The research paper further develops a framework for digital transformation in waqf management incorporating, Digital Literacy Foundation which is essential skills for Waqf professionals, aligned with WAMSI's digital platform, WAMSI-Specific Skills: Training in WAMSI's features, digital asset management, and online donor engagement, Advanced Digital Competencies: Data analytics, digital marketing, and cyber security skills for enhanced Waqf operations, Change Management and Leadership: Equipping Waqf leaders to drive digital transformation, leveraging WAMSI, Implementation and Evaluation: Phased rollout, monitoring, and assessment framework. This research employs a mixed-methods approach, combining surveys, interviews, and focus groups to, Assess digital skills gaps among Indian Waqf professionals, Identify best practices in digital capacity building. Overall, this study aims to enhance Waqf professionals' digital competencies, Optimize WAMSI adoption and utilization, Improve Waqf institutions' governance and operational efficiency, Amplify social impact through effective digital engagementThis study contributes to India's Waqf sector development, providing a tailored framework for Waqf professionals to leverage WAMSI effectively, driving digital transformation and sustainability.